Oxidative stress and muscle cell damage biomarkers monitoring in male volleyball athletes during a competitive season - Ferreira Antunes Neto, J. M.; Bergo Nader, B.; Passini Sodré Siviero, I. M.; Padovani, R. M. (Brazilian Journal of Biomotricity, 2013)
This study evaluated the oxidative stress markers in volleyball players along three distinct phases of a championship to determine if they were able to reflect the different stress levels (phase 1: low intensity exercises; phase 2: increase in load of training and start of the championship; phase 3: decreases in sessions and load of training and the final phase of the championship). We measured the antioxidant status (catalase-CAT, glutathione reductase-GR activities and plasma total sulfhydryl groups-TSG concentration); the oxidant status (reactive carbonyl derivatives-RCD and thiobarbituric acid reactive substances-TBARS concentrations); and assessed the muscular damage levels through plasma creatine kinase (CK) activity in blood samples of non-trained subjects (n = 9) and volleyball players (n = 9). We found at phase 2 a significant increase of plasma RCD concentration and an evident tendency of increase in plasma CK activity. At this moment, the antioxidant enzyme activities decreased to the lowest levels. The decrease in overload during phase 3 induced a significant up-regulation of enzyme activities and an important decrease of RCD in comparison with phase 2. The biomarkers analyzed reflected the different degree of stress imposed during the championship and showed that the players presented the lowest oxidative stress level combined with the best performance parameters during the principal phase (phase 3) of the championship.